2019
DOI: 10.1016/j.palaeo.2019.109371
|View full text |Cite
|
Sign up to set email alerts
|

Wind variability over the northern Indian Ocean during the past 4 million years – Insights from coarse aeolian dust (IODP exp. 359, site U1467, Maldives)

Abstract: The lithogenic fraction of carbonate drift sediments from IODP Exp. 359 Site U1467 (Maldives) provides a unique record of atmospheric dust transport over the northern Indian Ocean during the past 4 Myr. Grain-size data provide proxies for dust flux (controlled by source area aridity) as well as wind transport capacity (wind speed). Entrainment and long-range transport of dust in the medium to coarse silt size range is linked to the strength of the Arabian Shamal winds and the occurrence of convective storms wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…It is also interesting that the maximum aeolian grain size record from a nearby site in the Maldives (IODP Exp. 359 site U1467; Lindhorst et al 2019;Fig. 5f) does not bear many similarities to the Chinese loess grain size record.…”
Section: The New ε Nd Record Of Hi1808-gpc04 and Comparison With Odp 758 And Sk 129mentioning
confidence: 96%
“…It is also interesting that the maximum aeolian grain size record from a nearby site in the Maldives (IODP Exp. 359 site U1467; Lindhorst et al 2019;Fig. 5f) does not bear many similarities to the Chinese loess grain size record.…”
Section: The New ε Nd Record Of Hi1808-gpc04 and Comparison With Odp 758 And Sk 129mentioning
confidence: 96%
“…Therefore, the Maldives Inner Sea acts as a natural sediment trap best suited for dust deposition 7 . Evidence of sedimentology, geochemistry and morphology of sediment grains from Site U1467 all suggest that the lithogenic fraction is primarily dominated by eolian materials 25,26 . Consequently, the lithogenic fraction at Site U1467 is of eolian origin, and the contribution of fluvially-derived material supplied by currents from the Arabian Sea and the Bay of Bengal can be neglected [24][25][26] .…”
Section: Sr and Nd Isotopes And Sediment Provenance Discriminationmentioning
confidence: 99%
“…Evidence of sedimentology, geochemistry and morphology of sediment grains from Site U1467 all suggest that the lithogenic fraction is primarily dominated by eolian materials 25,26 . Consequently, the lithogenic fraction at Site U1467 is of eolian origin, and the contribution of fluvially-derived material supplied by currents from the Arabian Sea and the Bay of Bengal can be neglected [24][25][26] . Previous studies have demonstrated that the input of eolian dust to the Arabian Sea is primarily linked to the southwesterly monsoonal winds and subordinated northwesterly Shamal winds, both during the summer monsoon season [26][27][28][29] .…”
Section: Sr and Nd Isotopes And Sediment Provenance Discriminationmentioning
confidence: 99%
“…The influence of Earth orbital forcing on the long-term evolution of Indian monsoon has been recorded in deep-sea cores, lake sediments and stalagmites (Ziegler et al, 2010a;Cai et al, 2010;An et al, 2011). Previous researches demonstrated that the climate evolution of Indian monsoon is dominated by precession (~23 ka), obliquity (~41 ka) and eccentricity (~100 ka) cycles (e.g., Clemens et al, 1996;Clemens and Prell, 2003;Kelly et al, 2005;Kunkelova et al, 2018;Lindhorst et al, 2019;Lu et al, 2020). Previous orbital-scale studies of the ISM mainly used proxies of phytoplankton (G. bulloides) from the northern Arabian Sea (Prell et al, 1984;Prell and Van Campo, 1986;, grain size (Clemens and Prell, 1990;Krissek and Clemens, 1992), Ti/Al and excess Ba MAR (Shimmield et al, 1990), biogenic opal and organic carbon MAR (Murray and Prell, 1991).…”
Section: Orbital-scale Variabilitymentioning
confidence: 99%